The Japanese adjectives Jouzu and Tokui - Zin, Zaid Mohd; Hamzah, Nor Sahayu; Rodi, Rozita Che (Human Resource Management Academic Research Society, 2023)
This study is a semantic study that explores the genre of meaning in general. The use of adjective lexicons with synonymous meanings in Japanese sentences often confuses learners due to the differences meaning in comparison to their mother tongue. The objective of this study is to discuss the similarities and differences of the usage of the synonymous adjectives between Japanese and Malay language in the construction of sentences. The data for the study is selected from Nihongo Hyougen Bunkei Jiten and ejje.weblio.jp website. The textual analysis of the study was carried out based on Lado's (1966) theory. The findings of this study underline four differences in the vocabulary systems between Japanese and Malay language. The adjectives jouzu and tokui are synonymous in term of meanings but are different in their usage. Japanase adjectives changes the form according to the timeline of the tenses meanwhile the Malay adjectives changes form depends on the Malay adverb used. In conclusion, Japanese adjectives keiyoushi-I and keiyoushi-Na have four features while the Malay adjectives have nine features. The outcomes of this study can be used as a reference for teachers and learners to enhance the usage of adjectives jouzu and tokui in Japanese teaching and learning. Further studies on other Japanese adjectives also should be carried out.